The reliability of active motor card instruments as an evaluation of motor skills of elementary school children ages 10-12 years - Muhammad Naufal Indanus Syairozi; Nurrul Riyad Fadhli (Journal of Physical and Outdoor Education, 2025)
This study aims to test the reliability of the Active Motor Card instrument in measuring the motor skills of children aged 10-12 years. Motor skills play an important role in physical development and support the achievement of the Sustainable Development Goals (SDGs) related to health. The research design used was the development of instruments with the main focus of research conducting reliability tests. The research population is students at SDN Sumbersari 3 using total sampling techniques. The sample in this instrument trial was all students in grades 4-6 with a total of 78 students. The test results were then analyzed using Cronbach's Alpha and Corrected Item-Total Correlation methods. The Active Motor Card subtest consists of locomotor and non-locomotor skills. The results of the reliability test showed a value of α = 0.949, indicating high internal consistency. In conclusion, the Active Motor Card is a reliable instrument to assess the motor skills of children aged 10-12 years and is suitable for monitoring children's motor development systematically. Further research with a wider sample is recommended for further development.